Numerical demonstration of triangular shaped photonic crystal fibre‐based biosensor in the Terahertz range - Kawsar Ahmed; Bikash Kumar Paul; Fahad Ahmed; Md. Asaduzzaman Jabin; Muhammad Shahin Uddin (IET Optoelectronics, 2021)
Abstract In this study, a novel design of microstructure ring‐based triangular mold photonic crystal fibre has been numerically investigated and introduced as an alcohol sensor in Terahertz (THz) band region to get a very high relative‐sensitivity and negligible confinement‐loss profile. Perfectly Matched Layer contains circular air holes with a semi‐poly crystalline symmetric core structure in the triangular cladding region. The entire evaluation process is done by analyzing 2,888,310 mesh elements with the finite element method. Also, the proposed model is justified for an operating frequency of the THz band gap between 1.4 THz and 3.5 THz along with a base material of TOPAS. Last of all, the relative sensitivity profiles of the proposed model are 79.39%, 79.99%, and 80.27% respectively to the water, ethanol, benzene at an optimum frequency of 1.5 THz. In fact, the most optimum performance indicators are 1.18 × 10−12 dB/m, 1.8 × 10−5 µm2, 80%, 0.1 ps/THz/cm and 0.1‐1.5 respectively to the confinement‐loss (Lc), effective area (Aeff), power fraction (η′), dispersion (β2) and V‐Parameter (Veff) at the following optimum frequency for the proposed structure. By evaluating these performance profiles, the proposed model can prove itself a better choice than any other prior model in the field of sensing.